Sistem Diagnosis Penyakit Antraknosa Pada Cabai Menggunakan Metode Fuzzy Tsukamoto - Ganda Adi Khotarto; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Red chili pepper (Capsicum annum l.) is one of the many vegetable commodities consumed by the people of Indonesia, both as a food and flavoring the fulfillment of nutrition. Chilli needs in Indonesia from year to year has increased steadily. However, up to this time chili production in Indonesia is still not able to satisfy the needs of the community. This is because the fluctuating production with low productivity belong. loss can achieve 40-50%. Directorate General of Horticulture mentions that in the year 2012, the level of damages to crops of chili in Indonesia caused by pests and diseases reach 35%. Tsukamoto Fuzzy method is a method that has a tolerance on the data and very flexible. The advantages of the method are namely Tsukamoto is intuitive and can give feedback based on information that is not accurate, qualitative, and ambiguous. The required variable in this study are antraknosa symptoms on chili. The accuracy of the test results was 88.33%.